Prognostic value of proximal left coronary artery flow velocity detected by transthoracic Doppler echocardiography() - Morofuji, Toru (Int J Cardiol Heart Vasc, 2018)
BACKGROUND: Lesions in the proximal left coronary artery (LCA) are associated with a poor prognosis compared with other lesional sites. Transthoracic Doppler echocardiography (TTDE) can help to detect proximal LCA flow, and an accelerated coronary flow velocity (CFV) indicates the presence of proximal LCA lesions. This study aimed to investigate the prognostic value of CFV in the proximal LCA measured by TTDE. METHODS: We enrolled 1472 consecutive hemodynamically stable patients with known or suspected heart disease whose CFV was successfully detected using TTDE accompanied by routine echocardiography between 2008 and 2011. The primary outcome was cardiac death (acute myocardial infarction, heart failure, or sudden cardiac death) and patients were followed up over a median of 6.3 years. RESULTS: Overall, 42 cardiac deaths (3%) were observed. An increased CFV was significantly associated with the outcome in several models based on potential confounders (age, rate pressure product, Framingham Risk Score, diabetes, coronary artery disease, hemoglobin, brain natriuretic peptide, estimated glomerular filtration rate, left ventricular mass, left ventricular ejection fraction, and E/e′). Using a receiver operating characteristic curve analysis, the optimal cut-off value for the CFV to the association of the outcome was 37 cm/s (area under the curve, 0.70; sensitivity, 82%; specificity, 62%). In sequential Cox proportional hazards models, the CFV added incremental prognostic information to the clinical and basic echocardiographic parameters (chi-squared: 110.7 to 146.6, P < 0.01). CONCLUSIONS: An increased CFV in the proximal LCA was associated with cardiac death, incremental to the clinical and basic echocardiographic parameters.